Ciliwung River Resource Management And Ecotourism By The Ciliwung Community In Depok - Ahmad Naisaburi Bintang Dhia; Rizki Nurul Nugraha; Rai Riya (West Science Information System and Technology, 2024)
The research entitled “CILIWUNG RIVER RESOURCE MANAGEMENT AND ECOTOURISM BY THE CILIWING COMMUNITY IN DEPOK” aims to identify resource management and eco-ecosystems in the Ciliwung River, and to find out what obstacles to resource and ecosystems management in Ciliwing Depok River. The research uses qualitative methods, with descriptive qualitational emphasis and SWOT analysis. Data collection is carried out with field observations, interviews, and literature studies. The results of the research show that the river resource management strategy implemented has the potential to be an attractive ecosystem destination. Through the environmental conservation, recreation, and education methods carried out by KCD, the river can provide significant benefits to the surrounding community and its surrounding environment. Tourist components such as attractions, accessibility, and facilities around the river are important factors in attracting tourists and supporting sustainable ecosystem development.